Le visage et le masque. Ellie Papadimitriou, une intellectuelle de gauche - Ioanna Petropoulou (L'Atelier du CRH)
By following the case of Elli Papadimitriou (1900-1993), this article discusses the issue of the relation between literary creativity and political engagement. Originating from a bourgeois family of Smyrna, Papadimitriou relocated in Athens after 1922. During the Interwar period, she became a member of the Communist Party of Greece, enrolling at the same time in the British Security Services at the Middle East. In order to understand her own personal story, one must fully take into account the exact circumstances in which the communists of both sexes experienced Greece throughout the 20th century. As a left-wing poet, Ellie Papadimitriou has been persecuted and censored by the wright-wing governments after the Second World War. She introduced oral history in Greece through her ‘magnum opus’ The Common Language −a collection of oral testimonies “from the perspective of the defeated” of Asia Minor, the German Occupation and Greek Civil War. Due to her dual political engagement, she attempted to conceal her true visage and not to leave any traces neither to her contemporaries nor to future generations. The Biography of Elli Papadimitriou brings to light a large part of her “secret life”, by way of an archaeological excavation